Analysis of cfDNA fragmentomics metrics and commercial targeted sequencing panels - Helzer, Kyle T.; Sharifi, Marina N.; Sperger, Jamie M.; Chrostek, Matthew R.; Bootsma, Matthew L.; Reese, Shannon R.; Taylor, Amy; Kaufmann, Katie R.; Krause, Hannah; Schehr, Jennifer; Sethakorn, Nan; Kosoff, David; et al. (Nature Communications, 2025)
Fragmentomics based analysis of cell-free DNA (cfDNA) has recently emerged as a method to infer epigenetic and transcriptional data. Many of these reports analyze whole genome sequencing (WGS) which is not readily available clinically. Targeted exon panels are used for clinical cfDNA variant calling. In this report, we conduct an investigation of multiple published fragmentomics methods for WGS, but on cancer exon panels. We find that strategies utilizing normalized depth metrics, as well as all exons present on the panel, generally allow for better prediction of cancer phenotypes across a range of tumor fractions, though other metrics work particularly well in specific applications. Additionally, genes from commercial clinical targeted sequencing panels could be similarly employed for cancer phenotyping with a minimal decrease in performance despite their smaller genomic coverage. These results suggest that fragmentomics-based analysis of cfDNA can utilize targeted sequencing panels and does not necessarily require additional WGS.